Sistem Pakar Menu Sehat Berdasarkan Golongan Darah Menggunakan Metode Certainty Factor - Asikin, Butsiarah; Suhada, Sitti (Jurnal Teknik, 2024)
A healthy menu refers to a list of foods that can provide all the essential nutrients for the body, such as carbohydrates, proteins, fibers, fats, vitamins, and minerals, in balanced proportions. The types of food recommended for consumption must be in accordance with blood type, in order to affect the body's metabolism. The purpose of this study was to develop a healthy menu expert system based on blood type using the certainty factor method. The certainty factor method is used to determine the level of certainty in providing food recommendations that are in accordance with blood type in order to support health. The research approach applied is the waterfall method, which includes several stages, such as needs analysis, system design, coding, testing, and implementation. Based on the research conducted, a healthy menu expert system based on blood type using the certainty factor method was successfully developed. The results of the black box test showed that the alpha testing test obtained an average value of 4.3, which is included in the valid category, while the beta testing test produced an average value of 4.0, which is also valid. After being tested, this expert system had an accuracy of 91.6%, which indicates that the system provides healthy menu recommendations that are appropriate, accurate, and useful.